2023
DOI: 10.1093/jas/skad108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lasalocid, narasin, or virginiamycin supplementation on rumen parameters and performance of beef cattle fed forage-based diet

Abstract: Two experiments were designed to evaluate the impacts of supplementing lasalocid, narasin, or virginiamycin on rumen fermentation parameters, apparent nutrient digestibility, and blood parameters (Exp. 1), as well as feed intake and performance (Exp. 2) of Nellore cattle consuming a forage-based diet. In Exp. 1, thirty-two rumen-fistulated Nellore steers (initial shrunk BW = 355 ± 4.4 kg) were assigned to a randomized complete block design. Within block, animals were randomly assigned to 1 of 4 treatments: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 61 publications
2
7
0
1
Order By: Relevance
“…Liver abscesses are more often reported in highconcentrate feedlot diets, which is not the case in the present study. Shifts in ruminal fermentation due to virginiamycin supplementation towards more propionate and less lactate are reported for animals fed high-concentrate diets [43] but not for forage-based diets [8,38,44]. Results regarding rumen parameters from the present study corroborate the latter authors.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Liver abscesses are more often reported in highconcentrate feedlot diets, which is not the case in the present study. Shifts in ruminal fermentation due to virginiamycin supplementation towards more propionate and less lactate are reported for animals fed high-concentrate diets [43] but not for forage-based diets [8,38,44]. Results regarding rumen parameters from the present study corroborate the latter authors.…”
Section: Discussionsupporting
confidence: 88%
“…Livestock producers worldwide constantly seek ways to enhance the efficiency and profitability of their production systems [1,2]. Several authors have reported increased efficiency and/or performance of animals fed feed additives, such as ionophores and nonionophore antibiotics, in both high-concentrate [3][4][5][6] and forage-based [7,8] diets. The latter studies, however, were carried out in housed facilities with animals fed in feed troughs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ionophores also results in better energy retention efficiency, use of nitrogen from the diet, mitigation of methane production, and lower occurrence of metabolic disorders ( McGuffey et al, 2001 ). Narasin is a monovalent ionophore that increases the concentration of ruminal propionate and total SCFA and reduces acetate:propionate ( Ac:Prop) ratio of animals consuming forage-based diets ( Polizel et al, 2020 ; Limede et al, 2021 ; Miszura et al, 2023 ). However, none of our earlier studies demonstrated an improvement in digestibility when narasin was given to animals eating diets based on forage, despite the fact that the forage quality varied between these studies ( Polizel et al, 2020 —average CP = 10.3%; Limede et al, 2021 —average CP = 17.6%; Soares et al, 2021 —CP = 20.8%; Miszura et al, 2023 —average = CP 12%).…”
Section: Introductionmentioning
confidence: 99%
“…Lasalocid has been shown to have positive effects on lipid metabolism in cows and sheep, including an increase in high-density lipoprotein (HDL) levels. Higher levels of HDL have been associated with a lower risk of cardiovascular disease, indicating the potential benefits of lasalocid supplementation in improving animal health and productivity ( 16 ). Recent literature reviews have highlighted the potential benefits of LAS supplementation for improving animal performance and welfare.…”
Section: Introductionmentioning
confidence: 99%